Different Sites of Alcohol Action in the NMDA Receptor GluN2A and GluN2B Subunits - Zhao, Yulin (Neuropharmacology, 2015)
The NMDA receptor is a major target of alcohol action in the CNS, and recent behavioral and cellular studies have pointed to the importance of the GluN2B subunit in alcohol action. We and others have previously characterized four amino acid positions in the third and fourth membrane-associated (M) domains of the NMDA receptor GluN2A subunit that influence both ion channel gating and alcohol sensitivity. In this study, we found that substitution mutations at two of the four corresponding positions in the GluN2B subunit, F637 and G826, influence ethanol sensitivity and ion channel gating. Because position 826 contains a glycine residue in the native protein, we focused our attention on GluN2B(F637). Substitution mutations at GluN2B(F637) significantly altered ethanol IC(50) values, glutamate EC(50) values for peak (I(p)) and steady-state (I(ss)) current, and steady-state to peak current ratios (I(ss):I(p)). Changes in apparent glutamate affinity were not due to agonist trapping in desensitized states, as glutamate I(ss) EC(50) values were not correlated with I(ss):I(p) values. Ethanol sensitivity was correlated with values of both I(p) and I(ss) glutamate EC(50), but not with I(ss):I(p). Values of ethanol IC(50), glutamate EC(50), and I(ss):I(p) for mutants at GluN2B(F637) were highly correlated with the corresponding values for mutants at GluN2A(F636), consistent with similar functional roles of this position in both subunits. These results demonstrate that GluN2B(Phe637) regulates ethanol action and ion channel function of NMDA receptors. However, despite highly conserved M domain sequences, ethanol's actions on GluN2A and GluN2B subunits differ.